Annual elk calf survival in a multiple carnivore system. Issue 8 (10th August 2016) - Eacker, Daniel R.; Hebblewhite, Mark; Proffitt, Kelly M.; Jimenez, Benjamin S.; Mitchell, Michael S.; Robinson, Hugh S.
ABSTRACT: The realized effect of multiple carnivores on juvenile ungulate recruitment may depend on the carnivore assemblage as well as compensation from forage and winter weather severity, which may mediate juvenile vulnerability to predation in ungulates. We used a time‐to‐event approach to test for the effects of risk factors on annual elk ( Cervus canadensis ) calf survival and to estimate cause‐specific mortality rates for 2 elk populations in adjacent study areas in the southern Bitterroot Valley, Montana, USA, during 2011–2014. We captured and radio‐tagged 286 elk calves: 226 neonates, and 60 6‐month‐old calves. Summer survival probability was less variable than winter ( P  = 0.12) and averaged 0.55 (95% CI = 0.47–0.63), whereas winter survival varied more than summer and significantly across study years ( P  = 0.003) and averaged 0.73 (95% CI = 0.64–0.81). During summer, elk calf survival increased with biomass of preferred forage biomass, and was slightly lower following winters with high precipitation; exposure to mountain lion ( Puma concolor ) predation risk was unimportant. In contrast, during winter, we found that exposure to mountain lion predation risk influenced survival, with a weak negative effect of winter precipitation. We found no evidence that forage availability or winter weather severity mediated vulnerability to mountain lion predation risk in summer or winter (e.g., an interaction), indicating that the effect of mountain lion predation was constant regardless of spatial variation in forage or weather. Mountain lions dominated known causes of elk calf mortality in summer and winter, with estimated cause‐specific mortality rates of 0.14 (95% CI = 0.09–0.20) and 0.12 (95% CI = 0.07–0.18), respectively. The effect of carnivores on juvenile ungulate recruitment varies across ecological systems depending on relative carnivore densities. Mountain lions may be the most important carnivore for ungulates, especially where grizzly bears ( Ursus arctos ) and wolves ( Canis lupus ) are rare or recovering. Finally, managers may need to reduce adult female harvest of elk as carnivores recolonize to balance carnivore and ungulate management objectives, especially in less productive habitats for elk. © 2016 The Wildlife Society.